Type I interferons have opposing effects during the emergence and recovery phases of colitis. Issue 9 (25th August 2014) - Rauch, Isabella; Hainzl, Eva; Rosebrock, Felix; Heider, Susanne; Schwab, Clarissa; Berry, David; Stoiber, Dagmar; Wagner, Michael; Schleper, Christa; Loy, Alexander; Urich, Tim; Müller, Mathias; et al.
<x xml:space="preserve">Abstract</x> The contribution of the innate immune system to inflammatory bowel disease (IBD) is under intensive investigation. Research in animal models has demonstrated that type I interferons (IFN‐Is) protect from IBD. In contrast, studies of patients with IBD have produced conflicting results concerning the therapeutic potential of IFN‐Is. Here, we present data suggesting that IFN‐Is play dual roles as regulators of intestinal inflammation in dextran sodium sulfate (DSS)‐treated C57BL/6 mice. Though IFN‐Is reduced acute intestinal damage and the abundance of colitis‐associated intestinal bacteria caused by treatment with a high dose of DSS, they also inhibited the resolution of inflammation after DSS treatment. IFN‐Is played an anti‐inflammatory role by suppressing the release of IL‐1β from the colon MHC class II+ cells. Consistently, IL‐1 receptor blockade reduced the severity of inflammation in IFN‐I receptor‐deficient mice and myeloid cell‐restricted ablation of the IFN‐I receptor was detrimental. The proinflammatory role of IFN‐Is during recovery from DSS treatment was caused by IFN‐I‐dependent cell apoptosis as well as an increase in chemokine production and infiltrating inflammatory monocytes and neutrophils. Thus, IFN‐Is play opposing roles in specific phases of intestinal injury and inflammation, which may be important for guiding treatment strategies in patients.